Geoturismo e geoparques na região central do Rio Grande do Sul - Brasil - Marczewski, Richard Kohler (2023)
The central region of the Rio Grande do Sul state - Brazil features several geotouristic attractions and development potential under initiatives such as the aspiring geoparks Quarta Colonia e Cacapava as well as the project Geopark Raizes de Pedra. These areas are characterized by a large geodiversity, featuring many geoassets as well. At the center of these areas lies the city of Santa Maria, which has potential to be the gate city to the region, because it already features charachteristics for such, like services, infrastructure and accesses. Under this field of study, it was pursued to apply concepts developed still in the seventies in Europe for the evaluation of tourism centers that aim to nucleate initiatives to develop the region as a whole. In addition to this methodology we aimed, by means of a questionnaire and interviews, to understand the dynamics of these areas, and subsequently to propose centers of tourism development for a better regional development. Thus this work had two approaches to provide a theroretical framework for the proposals, namely tourism and geographic charachteristics.